2018
DOI: 10.1021/acssuschemeng.7b02913
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Reduction of CO2 to Formate at Low Overpotentials Achieved by a Mesoporous Tin Oxide Electrocatalyst

Abstract: A well-ordered mesoporous SnO2 prepared by a simple and inexpensive nanocasting method was used as catalysts for the electrochemical reduction of CO2 to formate. The as-prepared catalyst exhibited high activity toward CO2 reduction, which was capable of reducing CO2 to formate with 38% of Faradaic efficiency (FE) at an applied overpotential as low as 325 mV. The maximum FE for formate generation (75%) was achieved at an applied potential of −1.15 V (vs RHE), accompanied by a high current density of 10.8 mA cm–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
91
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 74 publications
6
91
1
1
Order By: Relevance
“…Similar facet dependent DFT results with Sn, In and Bi catalysts were used as theoretical evidence to justify the catalytic activity of these catalysts for CO 2 RR . In addition, SnO 2 (110) is reported to play a positive role in dictating formate generation during CO 2 RR with a number of literatures with SnO 2 nanoparticle catalysts ascribing the importance of this facet …”
Section: Active Sites In Metal‐based Catalystssupporting
confidence: 52%
“…Similar facet dependent DFT results with Sn, In and Bi catalysts were used as theoretical evidence to justify the catalytic activity of these catalysts for CO 2 RR . In addition, SnO 2 (110) is reported to play a positive role in dictating formate generation during CO 2 RR with a number of literatures with SnO 2 nanoparticle catalysts ascribing the importance of this facet …”
Section: Active Sites In Metal‐based Catalystssupporting
confidence: 52%
“…[39] It can be observed from Figure 4a, the intensity ratio between defects and the resonant A 1g phonon (I defect /I A1g ) was maximized for FSP-SnO 2 -5 (I defect /I A1g = 1.36) followed by FSP-SnO 2 -7 (I defect /I A1g = 1.25) and the lowest was for FSP-SnO 2 -3 (I defect /I A1g = 1.02). [44] It has been reported that OHC sites, alongside the radicals, assists in the binding of CO 2 reactants, [25,38,45] as well as active sites to stabilize the formate anion radical intermediate. UV-vis carried out with FSP-SnO 2 -5 further indicated that these defects are not changing the electronic states of the catalyst ( Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, research has focused on the quest to make scalable active catalysts by developing novel nanostructures that can promote mass transport, present higher electrical conductivity as well as contain more active sites. [23,24] While oxygen vacancy defects were ascribed as beneficial for CO 2 RR to formate in prior reports, [23,25] to the best of our knowledge there exists no systematic investigation tuning these vacancies and associating the nature of such defects as well as correlation with CO 2 RR. [16][17][18][19][20] As such, it is becoming imperative to develop designer SnO 2 catalysts using scalable methods that would allow control over tuning the active sites for CO 2 RR.…”
mentioning
confidence: 99%
“…In this manuscript, we demonstrate, for the first time, a class of binary PdÀ Ni alloy nanoparticles over two different carbon supports showing exceptional enhancement of the formate oxidation reaction (FOR) performance in alkaline medium, compared to Pd/C. [9][10][11] Formate is further advantageous in terms of its nontoxic and environmentally friendly nature. The more active Pd catalytic sites of the nanoalloy helped to yield mass activities as high as 4.5 A mg À 1 Pd and 7.8 A mg À 1 Pd during FOR.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] With alkaline-type direct liquid fuel cells being given greater attention than acid-type fuel cells, [6][7] formate is an ideal fuel alternative to ethanol and methanol. [9][10][11] Formate is further advantageous in terms of its nontoxic and environmentally friendly nature. [9][10][11] Formate is further advantageous in terms of its nontoxic and environmentally friendly nature.…”
mentioning
confidence: 99%